2008
DOI: 10.1002/ejoc.200800230
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkylation through Cross‐Metathesis between Alkenes and (Perfluoroalkyl)propenes

Abstract: A new approach to perfluoroalkylated compounds based on cross-metathesis between perfluoropropenes and terminal alkenes has been developed. The reaction is catalysed with high efficiency and selectivity by the Hoveyda-Grubbs second-generation catalyst under mild reaction conditions. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…moieties) is more conveniently carried out with perfluoroalkylpropenes instead of perfluoroalkylethenes (Scheme ). The former are easier to access, as a twofold molar excess with respect to the alkene substrate is enough to ensure high yields of cross metathesis, and the reaction could be carried out in commonly used dichloromethane 14. This approach has been recently applied in the synthesis of fluorinated analogs of brassinosteroids15 and carboranes 16…”
Section: Introductionmentioning
confidence: 99%
“…moieties) is more conveniently carried out with perfluoroalkylpropenes instead of perfluoroalkylethenes (Scheme ). The former are easier to access, as a twofold molar excess with respect to the alkene substrate is enough to ensure high yields of cross metathesis, and the reaction could be carried out in commonly used dichloromethane 14. This approach has been recently applied in the synthesis of fluorinated analogs of brassinosteroids15 and carboranes 16…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy of the cross-metathesis procedure has prompted also us to investigate hitherto unexplored combinations of two different alkenes. Recently, we have shown that metathesis of various terminal alkenes with perfluoroalkylpropenes constitutes a simple and efficient approach for the synthesis of wide array of perfluoroalkylated compounds [ 4 ]. This methodology was then applied for the synthesis of perfluoroalkylated analogs of brassinosteroids [ 5 ], 17α-perfluoroalkylestradiols [ 6 ], perfluoroalkylcyclodextrins [ 7 ], and perfluoroalkylcarboranes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting solution was stirred at 42 °C for 3 h. Removal of the solvent in vacuo gave crude product, which was purified using flash chromatography (1/1 ethyl acetate/hexane, R f = 0.4). 61 Yield: 70%.…”
Section: Methodsmentioning
confidence: 99%